New species and new records of the family Phytoseiidae Berlese (Acari: Mesostigmata) from Saudi Arabia - Mirza, Jawwad Hassan; Kamran, Muhammad; Alatawi, Fahad Jaber (Zootaxa, 2024)
A new species of the genus Neoseiulus Hughes (Acari: Mesostigmata: Phytoseiidae), belonging to the paspalivorus species group, N. arabicus sp. nov., is described and illustrated based on females. Two species are reported as new to the mite fauna of Saudi Arabia—Kuzinellus blairi (McMurtry & Moraes) and Typhlodromus (Anthoseius) transvaalensis (Nesbitt). A key to the species in the transvaalensis species group of Typhlodromus (Anthoseius) is also provided.